Pengaruh Program Kepemilikan Saham Karyawan terhadap Kinerja Keuangan Perusahaan Publik di Indonesia - Violia Elsha Melinda; Madeline Lestari; Sammy Kristamuljana; Rathria Arrina Rachman (Studi Akuntansi dan Keuangan Indonesia, 2019)
Based on the Agency Theory, management (agent) is a party that is trusted by shareholders (principals) to manage the company and maximize shareholders’ value (Jensen and Meckling, 1976). In practice, conflicts between shareholders and managers are unavaidable because of differences in interests and information asymmetry called Agency Problem. One way to minimize agency problem is by applying Employee Stock Ownership Program (ESOP) which gives rights to company’s employees to own company’s share. Through ESOP, employees are expected to improve the performance and value of the company due to their stock ownership. The purpose of this study was to analyze the effect of the implementation of the ESOP program on company financial performance especially profitability as measured by ROE (Return on Equity) and ROA (Return on Assets). This study analyzes 62 listed companies in Indonesia adopting ESOP for the first time over 2009-2016. By using panel data regression method, the results of the study show that ESOP program has a significant negative effect on the profitability of the company.